THE ROLE OF ISMUBA SUBJECTS IN STRENGTHENING PROGRESSIVE MUHAMMADIYAH STUDENT PROFILE AT CIKAMPEK’S MUHAMMADIYAH VOCATIONAL SCHOOL OF INFORMATION AND TECHNOLOGY - Faizal Rahman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
This study aims to analyze the role of ISMUBA education in the progressive Muhammadiyah student profile at Cikampek. Muhammadiyah vocational school of information and technology. This study involves field research. It is concluded that with the recognition and understanding of ISMUBA in the progressive Muhammadiyah student profile in Cikampek Muhammadiyah vocational school of information and technology children gradually can recognize the vision and mission of Muhammadiyah. Also, they can understand their intentional life in this world and gradually find goals and happiness regarding their involvement in the organization. Therefore, educators should be more understood over the role of Muhammadiyah student profile in the progressive vocational school. Furthermore, with the role of ISMUBA in the educational unit, more optimal recognition is expected to form the true character of children, in which they can establish a better nation over the previous generation in an educational unit.